2016
DOI: 10.1016/j.ejca.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neoadjuvant chemotherapy with or without zoledronic acid on pathological response: A meta-analysis of randomised trials

Abstract: Purpose The addition of bisphosphonates to adjuvant therapy improves survival in postmenopausal breast cancer (BC) patients. We report a meta-analysis of four randomised trials of neoadjuvant chemotherapy (CT) +/− zoledronic acid (ZA) in stage II/III BC to investigate the potential for enhancing the pathological response. Methods Individual patient data from four prospective randomised clinical trials reporting the effect of the addition of ZA on the pathological response after neoadjuvant CT were pooled. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…However, this effect was only seen in postmenopausal and not in premenopausal women [86]. In the neoadjuvant setting, a similar trend was observed in postmenopausal patients [87].…”
Section: An Anti-tumor Effect Of Rankl Inhibition Mediated Via the Immentioning
confidence: 86%
“…However, this effect was only seen in postmenopausal and not in premenopausal women [86]. In the neoadjuvant setting, a similar trend was observed in postmenopausal patients [87].…”
Section: An Anti-tumor Effect Of Rankl Inhibition Mediated Via the Immentioning
confidence: 86%
“…Also, this study's meta-analysis provides the first data indicating a statistically significant benefit of the addition of ZOL to neoadjuvant CT in terms of pCR in postmenopausal patients with early breast cancer. The addition of ZOL to systemic therapy has shown a survival benefit in postmenopausal patients with low levels of reproductive hormones [17].…”
Section: Discussionmentioning
confidence: 99%
“…ZOL antiangiogenic effects in a neoadjuvant setting were also suggested, in prostate cancer patients, where ZOL treatment decreased the number of circulating endothelial and endothelial precursor cells, both markers of ongoing pathological neoangiogenesis [38]. Additionally, a meta-analysis of randomized trials of ZOL plus neoadjuvant chemotherapy in breast cancer patients revealed benefits in terms of pathological complete response in the breast only for postmenopausal women [39].…”
Section: Table 1 Bisphosphonate Classes and Their Anti-tumour And/ormentioning
confidence: 96%